2017
DOI: 10.18632/oncotarget.21585
|View full text |Cite
|
Sign up to set email alerts
|

The bromodomain and extraterminal domain inhibitor bromosporine synergistically reactivates latent HIV-1 in latently infected cells

Abstract: The long-lived latent HIV-1 reservoir is the major barrier for complete cure of Acquired Immune Deficiency Syndrome (AIDS). Here we report that a novel bromodomain and extraterminal domain (BET) inhibitor bromosporine which can broadly target BETs, is able to potently reactivate HIV-1 replication in different latency models alone and more powerful when combined with prostratin or TNF-α. Furthermore, the treatment with bromosporine induced HIV-1 full-length transcripts in resting CD4+ T cells from infected indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Inhibition of either cyclin-dependent kinase (CDK) 2 or CDK9 has been reported to suppress HIV-1 transcription or replication in vitro or in vivo(36-41). Previous reports show that bromodomain inhibitors induced reactivation of HIV-1 latency is dependent on CDK9 (24, 25). HIV-1 replication, in CDK2-knockdown macrophages-like cells derived from pluripotent stem cells, was significantly reduced(42).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Inhibition of either cyclin-dependent kinase (CDK) 2 or CDK9 has been reported to suppress HIV-1 transcription or replication in vitro or in vivo(36-41). Previous reports show that bromodomain inhibitors induced reactivation of HIV-1 latency is dependent on CDK9 (24, 25). HIV-1 replication, in CDK2-knockdown macrophages-like cells derived from pluripotent stem cells, was significantly reduced(42).…”
Section: Resultsmentioning
confidence: 93%
“…It is known that bromodomain-containing protein 4 (BRD4) competes P-TEFb and disrupts the interaction between Tat and P-TEFb, and forfeits the ability of Tat to trans-activate HIV-1 transcription(23-25). Given the important role of P-TEFb in regulating HIV gene expression, different BETi have been explored and tested to activate HIV-1 gene expression in latent models of primary CD4 + T cells, lymphocytic T cell lines and monocytic cell lines (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, inhibition of either cyclin-dependent kinase 2 (CDK2) or CDK9 suppresses HIV-1 transcription or replication (40)(41)(42)(43)(44)(45), and bromodomain inhibitor-induced reactivation of HIV-1 latency is dependent on CDK9 (30,31). In CDK2 knockdown macrophage-like cells derived from pluripotent stem cells, HIV-1 replication is significantly reduced (46).…”
Section: I-bet151 Activates Hiv-1 Gene Expression In Monocytic Cells mentioning
confidence: 81%
“…and LSF (39)(40)(41)(42). Likewise, the two identified inhibitors of BRD containing proteins, bromosporine and CPI-203, which target amongst others BRD4, which has been associated with the repressive SWI/SNF chromatin remodeling machinery (43), have been shown to efficiently reverse latency (33,34). Interestingly, both within this study newly discovered LRAs, SR-4370 and HPOB, target contrarily to the other four compounds, also the cytosolic deacetylase HDAC6, which has been found to be In conclusion, the described simplified screening for latency reversing agents in combination with an epigenetic-active drug library verified former studies and revealed two novel compounds, which may be used to induce HIV transcription in a broad range of latent viral reservoirs.…”
Section: Determination Of T-cell Activation and Side-effects On Othermentioning
confidence: 99%